Towards tolerance in liver transplantation. (October 2021) - Toti, L.; Manzia, T.M.; Sensi, B.; Blasi, F.; Baiocchi, L.; Lenci, I.; Angelico, R.; Tisone, G.
Abstract: Life-long immunosuppression has always been considered the key in managing liver graft protection from recipient rejection. However, it is associated with severe adverse effects that lead to increased morbidity and mortality, including infections, cardiovascular diseases, kidney failure, metabolic disorders and de novo malignancies. This explains the great interest that has developed in the concept of tolerance in recent years. The liver, thanks to its marked tolerogenicity, is to be considered a privileged organ: up to 60% of selected patients undergoing liver transplantation could safely withdraw immunosuppression. Highlights: Long-term survival in liver transplant patients is still low: the side effects of immunosuppression are the one main reason for this deficiency. The liver is immunologically privileged over other organs: for this reason, many studies have been carried out in recent decades to understand the best way to achieve complete tolerance. Withdrawal of immunosuppression can be safely achieved in up to 40% of selected liver transplant recipients. There is a need to define valid and safe biomarkers able to predetermine tolerance.